Organisational learning and employee engagement: The mediating role of supervisory support - O. Opeyemi Ogueyungbo; L. Moses Chinonye; Ebeguki Igbinoba; Odunayo Salau; Hezekiah Olubusayo Falola; Maxwell Olokundun (Cogent Business & Management, 2020)
This study examined the effect of organisational learning on employee engagement and the mediating influence of supervisory support in some selected pharmaceutical companies in Nigeria. The survey research design was adopted to assess the subject matter. Five hundred and forty-one hundred (541) respondents were surveyed across all the selected pharmaceutical companies in Nigeria with the usage of purposive and stratified sampling technique. Only four hundred and thirty-four (434) copies of questionnaire representing (80.2%) response rate were correctly filled, returned and analysed for this study. Structural Equation Model (AMOS 23) was adopted for the analysis of the mediating influence of supervisory support on organisational learning and efficacy of employee engagement to work and job task. The results from the test of hypotheses showed that supervisory supports significantly influence organisational learning and employee engagement (R2 = 0.813 p-value = 0.000). The study emphasised continuous supervisory training programs for employee's effective delivery of their roles should be given priority because of its role in mediating the relationship between organisational learning and employee engagement. The insights from this study would be of great value to the management of the pharmaceutical industry, and other stakeholders to develop and invest in organisational learning that will enhance job commitment and engagement of employees.
Keywords: 650; employee engagement; supervisory support; organisational learning